Cover Feature: Regioselective Glycosylation Strategies for the Synthesis of Group Ia and Ib Streptococcus Related Glycans Enable Elucidating Unique Conformations of the Capsular Polysaccharides (Chem. Eur. J. 71/2019). Issue 71 (6th November 2019) - Del Bino, Linda; Calloni, Ilaria; Oldrini, Davide; Raso, Maria Michelina; Cuffaro, Rossella; Ardá, Ana; Codée, Jeroen D. C.; Jiménez‐Barbero, Jesús; Adamo, Roberto
Abstract : To investigate the structural features determining the immunospecificity of Group B Streptococcus Ia and Ib polysaccharides, synthetic fragments were obtained by a newly developed regioselective approach. the Ia and Ib polysaccharides differ only in the connection of the Neu5Acα2‐3Gal side chain to the GlcNAc backbone unit. Combining synthesis, computational methods, and NMR spectroscopy it was found that this minimal difference drastically impacts on the conformational properties of Ia and Ib polysaccharides causing the exposure of different epitopes. More information can be found in the Full Paper by R. Adamo et al. on page 16277 .